The Spanish Jesuit Mission in Virginia, 1570-1572 - Lewis, Cliff (Published for the Virginia Historical Society by the University of North Carolina Press, 1953)
Foreword, by E. G. Swem.--An historical synthesis: a narrative summary of the documents.--The documents with their translations.--Ajacán and the Chesapeake.--Bibliography (p. 281-287)